ANALISIS KOINTEGRASI FAKTOR MAKRO EKONOMI INDEKS FTSE PADA BURSA EFEK INDONESIA PERIODE 2017-2022 - Vivin Hanitha; Tri Angreni; Hendra Hendra; Georgius Listens; Adrian Hidayat (Komunitas Dosen Indonesia, 2024)
This research was explain about analyzing and knowing the development of the global exchange stock price FTSE index by analyzing to the Indonesia’s Stock Exchange (BEI) and to determine cointegration between FTSE 100, data Inflation, USD/IDR exchange Rates, and Interest Rate. Combined to IHSG. Data collection method was data from 5 years starting from 2017 to 2022 on a monthly basis. The sampling method is nonprobability sampling with a sampling technique, namely purposive sampling. The analysis was carried out using the Johansen Cointegration Test and VECM test which processed by Eviews 10 software. Results showed no significancy short-term relationship between FTSE 100, Inflation, USD/IDR Exchange Rates, Interest Rate and Composite Stock Price Index (IHSG ). But, on the other side have a significant long-term relationship between them.